2007
DOI: 10.1117/12.711360
|View full text |Cite
|
Sign up to set email alerts
|

Immersion exposure tool for 45-nm HP mass production

Abstract: Canon has renewed its platform of exposure tools. The new platform, the FPA-7000, is designed to cover multiple generations. The lens performance of the FPA-7000AS5 achieves less than 6mλ, while that of the AS7 is estimated to be less than 4mλ. The illumination performance meets the target required for the 45nm node. The in-situ aberration monitor, called iPMI, attains the measurement repeatability of 1.45mλ. Focus and overlay units have improved process robustness. A solution tool for optimization is introduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2007
2007
2011
2011

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…The surface tension and viscosity of water are 72 mN/m and 1 mPa•s, respectively. This extremely high surface tension and low viscosity enable the immersion nozzle to keep water under a final lens (Kubo et al, 2007). On the other hand, it has been reported that a G2 fluid is easy to remain on a wafer (Sewell et al, 2007).…”
Section: Residual Fluid On a Wafermentioning
confidence: 99%
“…The surface tension and viscosity of water are 72 mN/m and 1 mPa•s, respectively. This extremely high surface tension and low viscosity enable the immersion nozzle to keep water under a final lens (Kubo et al, 2007). On the other hand, it has been reported that a G2 fluid is easy to remain on a wafer (Sewell et al, 2007).…”
Section: Residual Fluid On a Wafermentioning
confidence: 99%
“…This extremely high surface tension and low viscosity enable our liquid-film-flow nozzle to keep the immersion water under a final lens. 13) On the other hand, it has been reported that it is difficult to keep a G2 fluid under a final lens because of the low surface tension and the high viscosity.…”
Section: Residual Fluid On a Wafermentioning
confidence: 99%
“…This extremely high surface tension and low viscosity enable the immersion nozzle to keep water under a final lens (Kubo et al, 2007). On the other hand, it has been reported that a G2 fluid is easy to remain on a wafer (Sewell et al, 2007).…”
Section: Residual Fluid On a Wafermentioning
confidence: 99%